Composition, Structure, and Digestive Dynamics of Milk From Different Species—A Review - Roy, Debashree; Ye, Aiqian; Moughan, Paul J.; Singh, Harjinder (Frontiers in Nutrition, 2020)
Background The traditional dairy-cattle-based industry is becoming increasingly diversified with milk and milk products from noncattle dairy species. The interest in noncattle milks has increased because there have been several anecdotal reports about the nutritional benefits of these milks and reports both of individuals tolerating and digesting some noncattle milks better than cattle milk and of certain characteristics that noncattle milks are thought to share in common with human milk. Thus, noncattle milks are considered to have potential applications in infant, children, and elderly nutrition for the development of specialized products with better nutritional profiles. However, there is very little scientific information and understanding about the digestion behavior of noncattle milks. Scope and approach The general properties of some noncattle milks, in comparison with human and cattle milks, particularly focusing on their protein profile, fat composition, hypoallergenic potential, and digestibility, are reviewed. The coagulation behaviors of different milks in the stomach and their impact on the rates of protein and fat digestion are reviewed in detail. Key findings and conclusions Milks from different species vary in composition, structure, and physicochemical properties. This may be a key factor in their different digestion behaviors. The curds formed in the stomach during the gastric digestion of some noncattle milks are considered to be relatively softer than those formed from cattle milk, which is thought to contribute to the degree to which noncattle milks can be easily digested or tolerated. The rates of protein and fat delivery to the small intestine are likely to be a function of the macro- and micro-structure of the curd formed in the stomach, which in turn is affected by factors such as casein composition, fat globule and casein micelle size distribution, and protein-to-fat ratio. However, as no information on the coagulation behavior of noncattle milks in the human stomach is available, in-depth scientific studies are needed in order to understand the impact of compositional and structural differences on the digestive dynamics of milks from different species.